1971
DOI: 10.1002/1097-0142(197108)28:2<519::aid-cncr2820280234>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome studies in a “cancer family”

Abstract: A family with a high incidence of malignant disease has been followed for 11 years. Thirty‐seven of the 405 members of the family have had some type of malignant process. The most common types of malignancy were carcinoma of the breast, sarcoma, and acute leukemia. Cytogenetic studies were performed on the peripheral blood of 27 members of the family. Increased numbers of abnormal chromosomes were not consistently seen, although some members of the family seemed to have more aneuploidy than would be expected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Members of the 4 families initially reported have been followed up for a number of years and further cancers have developed (Li & Fraumeni, 1982). Other kindreds showing a similar array of tumours have been reported (Bottomly et al, 1971;Lynch et al, 1978;Blattner et al, 1979;Pearson et al, 1982;Duncan & Miller, 1983), and it has been suggested that there is a role for surveillance programmes aimed at early diagnosis and treatment amongst these families (Li & Fraumeni, 1975, 1982. However, all these kindreds have been ascertained by chance, or by investigating the extended pedigree of cases with a known family history of cancer, for example, sibling pairs of soft tissue sarcoma.…”
mentioning
confidence: 99%
“…Members of the 4 families initially reported have been followed up for a number of years and further cancers have developed (Li & Fraumeni, 1982). Other kindreds showing a similar array of tumours have been reported (Bottomly et al, 1971;Lynch et al, 1978;Blattner et al, 1979;Pearson et al, 1982;Duncan & Miller, 1983), and it has been suggested that there is a role for surveillance programmes aimed at early diagnosis and treatment amongst these families (Li & Fraumeni, 1975, 1982. However, all these kindreds have been ascertained by chance, or by investigating the extended pedigree of cases with a known family history of cancer, for example, sibling pairs of soft tissue sarcoma.…”
mentioning
confidence: 99%
“…Since then, including our 2 cases, 59 patients in 24 families have been reported (Barry 1961;Bech-Hansen et al 1981;Bottomley et al 1971;Brenton et al 1980;Colyer 1979;Epstein et al 1970;Gilman et al 1985;Harmon and Morton 1966;Lee and Mackenzie 1964;Matejovsky 1977;McIntyre et al 1994;Miller and McLaughlin 1977;Miller 1968;Mulvihill et al 1977;Nassar and Gravanis 1981;Nishida et al 1994;Pohle et al 1936;Robbins 1967;Roberts and Roberts 1935;Salvati et al 1994;Schimke et al 1974;Smith et al 1980;Swaney 1973;Werner 1930). The authors collected data from 59 cases, including the age and sex of the patient, the anatomical site, and previous disorders, treatment, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Distributions differ by sex; the predominant tumors being breast cancer among affected females (53%), as opposed to sarcomas among males (41%). Considering both sexes, approximately 80% of these tumors consists of the following: sarcomas (29%); breast cancer (30%); brain tu- (6). larynx (3), prostate (2), pancreas ( I ) , and Hodgkins disease (1).…”
Section: Genetic Analysismentioning
confidence: 99%
“…36 There is no firm evidence that such inclusions are related to the presence of virus or to products of viral activity, and in fact, electron microscopic evidence is to the contrary. 3 5 3 3 6 Froelich and Lapham, l9 however, on the basis of tissue culture studies of gliomas, maintain that one category of acidophilic intranuclear inclusion may be virus-related.…”
Section: Pathologymentioning
confidence: 99%